Size emergence of nanostructures - Yin, Yang (2015)
Nowadays big career could be made from something small. The real future for engineers will be Nano size technology, this new field could make quite numbers of job opportunities because of its widely applications. The nanosize material has become such amazing while we study the properties. With the dimension limited from 1 until 100 Nm of nanoscale size level, we’re exploring more and more for nanotechnology and nanoscience. Through the nanotechnology, we’re aim to improve our productivity by using the advantages of the nanomaterial’s interesting properties and nanoscience give us more chance for those challenge we’re facing at present moment especially about the medication. Through the properties and self-assembly studies of nanomaterials, it has proved that the nanotechnology could provide a very wide range of potential products and application and because of this our lives and economy could be affected positively. No matter for medication or manufacturing, nanotechnology is leading a new evolution of the way we’re thinking of and the way of products producing. In a recent market research from Global Information Inc, by year 2018 it is expected to reach US$3.3 trillion for the annual worldwide market with nanotechnology products. And by year of 2015, there’s a needs for nanotechnology professionals employees up to 1 million according to National Nanotechnology Infrastructure Network. Improving environment could be another useful application of the nanotechnology. There’re big opportunities for these tiny size stuff, nanotechnology eventually will lead us to a much higher intelligent future.